Discovery of a novel Wolbachia in Heterodera expands nematode host distribution - Kaur, Taranjot; Brown, Amanda M.V. (Frontiers in Microbiology, 2024)
Bioinformatic sequence data mining can reveal hidden microbial symbionts that might normally be filtered and removed as contaminants. Data mining can be helpful to detect Wolbachia, a widespread bacterial endosymbiont in insects and filarial nematodes whose distribution in plant-parasitic nematodes (PPNs) remains underexplored. To date, Wolbachia has only been reported a few PPNs, yet nematode-infecting Wolbachia may have been widespread in the evolutionary history of the phylum based on evidence of horizontal gene transfers, suggesting there may be undiscovered Wolbachia infections in PPNs. The goal of this study was to more broadly sample PPN Wolbachia strains in tylenchid nematodes to enable further comparative genomic analyses that may reveal Wolbachia's role and identify targets for biocontrol. Published whole genome shotgun assemblies and their raw sequence data from 33 Meloidogyne spp. assemblies, 7 Globodera spp. assemblies, and 7 Heterodera spp. assemblies were analyzed to look for Wolbachia. No Wolbachia was found in Meloidogyne spp. and Globodera spp., but among seven genome assemblies for Heterodera spp., an H. schachtii assembly from the Netherlands was found to have a large Wolbachia-like sequence that, when re-assembled from reads, formed a complete, circular genome. Detailed analyses comparing read coverage, GC content, pseudogenes, and phylogenomic patterns clearly demonstrated that the H. schachtii Wolbachia represented a novel strain (hereafter, denoted wHet). Phylogenomic tree construction with PhyloBayes showed wHet was most closely related to another PPN Wolbachia, wTex while 16S rRNA gene analysis showed it clustered with other Heterodera Wolbachia assembled from sequence databases. Pseudogenes in wHet suggested relatedness to the PPN clade, as did the lack of significantly enriched GO terms compared to PPN Wolbachia strains. It remains unclear whether the lack of Wolbachia in other published H. schachtii isolates represents the true absence of the endosymbiont from some hosts.